Knowledge and Practices of Student Nurses towards Prevention and Management of Pressure ulcers in Allied Hospitals of Rawalpindi Medical University - Nimra Ghafoor, Rabiya Munir, Inayat Mumtaz Khan Niazi, Faryal Azhar (Journal of Rawalpindi Medical College, 2021)
Introduction: Pressure ulcer is a common preventable complication of prolonged hospitalisation. Although debilitating, but preventable through timely assessment and proper management. This study was conducted to access student nurse’s knowledge and practices towards the prevention and management of pressure ulcers. Materials and Methods: A cross-sectional study was conducted at Nursing Schools of Holy Family Hospital and Benazir Bhutto Hospital Allied with Rawalpindi Medical University. A pre-tested self-designed questionnaire was filled by 264 students selected through the non-probability convenient sampling technique. Data were analysed using SPSS 21. P-value <0.01 was considered significant. Results: Mean percentage of Student nurse’s knowledge and practices were 58.7% 69.62% respectively. 21.7% of first-year students, 34.1% of second-year students, and 60.2% of third-year students had good knowledge. Correspondingly, 10.89% of first-year students, 32.9% of second-year students, and 56.2% of third-year students had good practice. There was a significant correlation between knowledge and practices i.e. r value is 0.92, the p-value is <0.000. Conclusion: Knowledge and Practices of Student Nurses towards the prevention and management of pressure ulcers was found to be average. The practices of students gradually improved as their knowledge improved throughout their years of education.